PENGELOLAAN KEUANGAN DAERAH MENUJU TRANSPARANSI DAN AKUNTABILITAS DI KANTOR DPPKAD KABUPATEN PATI - Dessy Monika Sari; Thalita Rifda Khaerani (Journal of Public Policy and Management Review, 2017)
Their decentralization gives local authorities to set their own financial management in a transparent and accountable according to the principles of good governance. This study was conducted to analyze the transparency and accountability of financial management, analyze the factors driving and inhibiting transparency and accountability of financial management in Pati regency DPPKAD with descriptive qualitative method. Data collected through interviews with informants and observations. This study uses the theory Djalil transparency of the legal framework, public access, inspection by the audit institution, early warning systems and community involvement. Warsito accountability theory of the political aspects, financial aspects, community satisfaction, consistency of office, the satisfaction of the apparatus, according to the rules of service. Theory factors driving and inhibiting transparency of Wiharto as well as driving and inhibiting accountability of Warsito. The results showed symptoms such as transparency of the legal framework, institutions examination, early warning systems have been met, the obstacles that the unavailability of public access through the internet, lack of public enthusiasm. There are symptoms of accountability obstacles that delayed absorption. The driving factor of transparency that is the function accuracy, clarity of rules, competition healthy environment, factors driving patterns of leadership accountability, freedom of the press, the role of stakeholders. Factors that still hamper the transparency that is overlapping rules, while inhibiting factor accountability does not impede financial management DPPKAD Pati regency. There are some suggestions that can be done such as training web management to support public access, dissemination to the public to attract enthusiasm, sanctions to SKPD that is behind schedule in sequestration budget, conduct competency-based training, provide rewards in particular, review the task function Bapermasdes and Governance to address regulatory overlap.